CASE STUDY OF INNOVATION BUSINESS MODEL TO PROMOTE SUSTAINABLE AGRICULTURE OF PRIVATE FARM IN TAIWAN - Shun-Cheng Chang; Lin, Chin-Chiuan (International Journal of Application on Economics and Business, 2023)
This study investigation modern sustainable agricultural business model of private farm in Taiwan. Enter the real field, understand the rural environment on the spot, and hope to bring substantial help to the current agricultural environment in Taiwan. Conduct Zhang-Jia farm as the case, based on local ecology, production and life to analyse the management characteristics of the farm. Combine with the theory of ideas explored in the literature to verify the relevance of its actual mode of operation and goals. Observe the local tribal ecology and industrial context to find problems, and compile various conceptual factors that affect the sustainable development of Taiwan's agriculture based on the literature. Through developing organic agriculture, promoting leisure agriculture, developing diversified agricultural products, promoting food agricultural education, and organized production and marketing groups as strategies. Through diversification activities, construct a field environmental relationship brimming with "agricultural production", "peasant life" and "rural ecology", and practice the concept of respect for nature. To maintain the survival of the farm and leave a beautiful homeland, further to increase agricultural production, increase income, maintain natural ecology, create the best areas for farming and living, attract more young people to return to the countryside, and to promote sustainable agriculture in Taiwan.